1967
DOI: 10.1149/1.2426589
|View full text |Cite
|
Sign up to set email alerts
|

Potentiostatic Current-Potential Measurements on a Platinum Electrode in a High-Purity Closed System

Abstract: In a high‐purity closed system, potential regions at which very slow reactions are rate‐controlling were accurately separated and measured. Tafel regions and the possible reaction mechanisms on a Pt electrode in helium‐saturated 1MH2SO4 normalfrom the H2 normalto the O2 formation reactions were determined. Effects of dermasorbed H and O atoms on transient and steady‐state reaction rates were shown. Maximum oxidizable and reducible impurity levels were quantitatively determined both in solution and as adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1967
1967
1982
1982

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…Measurements of the steady-state current density gave values comparable to those obtained by other workers using closed systems (9). A flat on one side of the cylinder was used for the optical measurements, although the laser source and double-pinhole lens-free optics of the ellipsometer enable measurements to be made on cylindrical surfaces.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…Measurements of the steady-state current density gave values comparable to those obtained by other workers using closed systems (9). A flat on one side of the cylinder was used for the optical measurements, although the laser source and double-pinhole lens-free optics of the ellipsometer enable measurements to be made on cylindrical surfaces.…”
Section: Methodssupporting
confidence: 72%
“…Vagramyan and Sutyagina (9) reported that alternating current can effect the grain size, brightness, and porosity of electrodeposited metals. Marchese (I0) showed that the superposition of a.c. on d.c. reduces internal stresses in electrodeposited nickel.…”
Section: The Effect Of Superimposedmentioning
confidence: 99%
“…As noted by Schuldiner et al (29), the dissolved oxygen penetrated more deeply than the derma when Pt was anodized at 1.7v because the effects of the dermasorbed oxygen could be detected for extended periods of time after the potential had been lowered below lv. This observation was explained by diffusion of absorbed oxygen from the metal interior into the dermasorbed region.…”
Section: Discussionmentioning
confidence: 73%
“…Brief aqua regia treatment reduced to to 50 msec, and three representative points were redetermined. (7). 1 of ref.…”
Section: Resultsmentioning
confidence: 98%